1997
DOI: 10.1016/s0014-5793(96)01258-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of S‐nitrosohaemoglobin by mass spectrometry

Abstract: Recent studies have demonstrated the biological importance of the interaction of S-nitrosothiols, which can be considered as nitric oxide (NO) protein donors, especially haemoglobin, at the level of Cys residues. It was recently proposed that S-nitrosohaemoglobin is formed within red blood cells and serves as a regulatory function. In human haemoglobin the ccrsubunit contains one Cys residue and the ß-subunit contains two Cys residues, one of which (ß-Cys 93 ) is highly reactive and conserved among species, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 19 publications
5
58
1
Order By: Relevance
“…The human β-subunit also contains a second Cys, βCys112, which can be S-nitrosylated in vitro (25). However, it has been established by previous mutagenic (26), mass spectrometric (27,28), and X-ray crystallographic analyses (29) that βCys93 is the predominant site of human β-subunit S-nitrosylation, consistent with the oxygenregulated disposition of NO within Hb in vivo (4,30,31). Additionally, the export of βCys93-derived NO bioactivity is based on an SNO cascade that involves the transfer of NO groups to RBC membrane proteins and to external sites that include smallmolecular-weight thiols (10,(14)(15)(16)(17).…”
Section: Resultsmentioning
confidence: 99%
“…The human β-subunit also contains a second Cys, βCys112, which can be S-nitrosylated in vitro (25). However, it has been established by previous mutagenic (26), mass spectrometric (27,28), and X-ray crystallographic analyses (29) that βCys93 is the predominant site of human β-subunit S-nitrosylation, consistent with the oxygenregulated disposition of NO within Hb in vivo (4,30,31). Additionally, the export of βCys93-derived NO bioactivity is based on an SNO cascade that involves the transfer of NO groups to RBC membrane proteins and to external sites that include smallmolecular-weight thiols (10,(14)(15)(16)(17).…”
Section: Resultsmentioning
confidence: 99%
“…To further examine the number of sites of NEM modification per Hb chain, ESI-MS was used, since it can sensitively differentiate mass changes as a result of NEM modification [14]. In both NEM-H Hb and NEM-L Hb samples, a peak was observed at 15,993 Da, corresponding to the mass of a β chain with one NEM molecule.…”
Section: Electrospray Ionization Mass Spectrometrymentioning
confidence: 99%
“…A variety of different methods, including FT-IR spectroscopy, ESI-MS and tandem MS, indicate NEM modification occurs at both β93 and α104 Cys residues and that the α104 residue is moderately reactive under relatively standard conditions [37]. Previously, modifications at Hb Cys residues other than β93 were only observed at high concentrations of modifying reagent [14,15,31]. Benesch and co-workers [31] observed that titration with an 100-fold molar excess of PMB results in the observation of 7.5 reactive -SH groups per mole of Hb, while lower PMB concentrations yield a value of 2.4 reactive -SH groups per mole of Hb.…”
Section: The α104 Cys Residue Is Modified By Nemmentioning
confidence: 99%
See 2 more Smart Citations